PENINGKATKAN MINAT BELAJAR MATEMATIKA MATERI TRANSFORMASI MELALUI PEMBELAJARAN MINIMALIS PADA SISWA KELAS IX SEMESTER 1 SMP N 2 GIRIMARTO - Sri Warsini (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
This Best Practice aims to increase interest in learning mathematics about Transformation Material through the application of MINIMALIST learning steps for class IX Semester 1 students at SMP N 2 Girimarto Wonogiri. Transformation material consists of many achievement indicators, namely Dilation, Reflection, Translation and Rotation of points, lines and planes. To make it easier for students to understand a lot of material and increase students' interest in learning this Transformation, the teacher uses the MINIMALIST learning method, which means MIN: Reading, Information (Literacy and Education), IMAL: Inquiry, Props Modeling, and IS: Peer tutor interaction and Pass it on. The results of the student interest in learning questionnaire before using MINIMALIST learning showed that there were 13 students (43.33%) with good criteria. The results of the student interest in learning questionnaire after using MINIMALIST learning were 17 students (56.67%) with good criteria. This illustrates that there has been an increase in interest in learning through MINIMALIST learning. From the increased interest in learning, the daily mathematics test score for Transformation material obtained after using MINIMALIST learning has an average score of 84.67%, namely there are 27 students or 90% who have completed the KKM and there are 3 students or 10% who have not completed the KKM. After providing remedial reinforcement, the average score was 85.67% and 30 students had completed the KKM or 100%. This means that MINIMALIST learning can be concluded to increase students' interest and learning outcomes in Mathematics on Transformation material.